2015
DOI: 10.1016/j.celrep.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Synapsin III Acts Downstream of Semaphorin 3A/CDK5 Signaling to Regulate Radial Migration and Orientation of Pyramidal Neurons In Vivo

Abstract: SummarySynapsin III (SynIII) is a phosphoprotein that is highly expressed at early stages of neuronal development. Whereas in vitro evidence suggests a role for SynIII in neuronal differentiation, in vivo evidence is lacking. Here, we demonstrate that in vivo downregulation of SynIII expression affects neuronal migration and orientation. By contrast, SynIII overexpression affects neuronal migration, but not orientation. We identify a cyclin-dependent kinase-5 (CDK5) phosphorylation site on SynIII and use phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…During these phases of development, the expression of isoforms derived from each synapsin gene varies. In accord with previous studies (Lohmann et al ., ; Porton et al ., ; Perlini et al ., ), synapsins I and II are expressed later in development (P7 to adulthood), while the peak of synapsin III expression occurs between P1‐P7 (Fig. E).…”
Section: Resultsmentioning
confidence: 91%
“…During these phases of development, the expression of isoforms derived from each synapsin gene varies. In accord with previous studies (Lohmann et al ., ; Porton et al ., ; Perlini et al ., ), synapsins I and II are expressed later in development (P7 to adulthood), while the peak of synapsin III expression occurs between P1‐P7 (Fig. E).…”
Section: Resultsmentioning
confidence: 91%
“…In untreated cells, filopodia number was inversely correlated to axonal nestin levels ( Figure 4G). After a low dose of Sema3a treatment (1nM for 5 minutes) (Perlini et al 2015), nestin-positive cells retracted growth cone filopodia significantly, whereas nestin-negative growth cones were not significantly affected by Sema3a during the 5 minute timeframe (shown in Figure 4B, quantified in Figure 4G). Area of the growth cone was not significantly altered in this short time frame as expected (Dent 2004), so we relied on the retraction of filopodia as our most sensitive measurement of Sema3a sensitivity.…”
Section: Nestin Protein Is Transiently Expressed Broadly Among Corticmentioning
confidence: 93%
“…Sema3a is upstream of cdk5 in neurons (Kobayashi et al 2014), and we thus utilized an in vitro bath application "Sema3a collapse assay" to test this idea. In cultured neurons, phosphorylation of cdk5 substrates and morphological changes in growth cones (Perlini et al 2015;Dent 2004) start within minutes of Sema3a exposure with the loss of growth cone filopodia, resulting ultimately in a collapsed growth cones with no filopodia. However, prior to complete growth cone collapse, Sema3a leads to retraction of individual filopodia (Dent 2004).…”
Section: Nestin Protein Is Transiently Expressed Broadly Among Corticmentioning
confidence: 99%
See 1 more Smart Citation
“…5) [81]. Similarly, another study revealed that semaphorin-3A (Sema3A)-induced activation of Cdk5 causes it to phosphorylate synapsin III, which regulates radial migration and orientation in vivo [83] (Fig. 5).…”
Section: Other Cdk5 Substrates Involved In Actin Dynamics (Talin Drementioning
confidence: 99%